A content analysis of chair designs in selected casual dining restaurants in UP Town Center in relation to comfort theory - Camu, Piolo Miguel M. (College of Home Economics, University of the Philippines Diliman, 2019)
The comfort that customers feel while sitting can be affected by their cultural affiliations, and most likely by human diversity which limits the successful application of standards (Robson, 2002). Using content analysis as a research design, the researcher analyzed the components of the dining chairs in selected casual dining restaurants in UP Town Center in relation to the diners' perception of comfort. Purposive sampling was used for the selection of casual dining restaurants, survey respondents, and key informants who participated in the focus group discussion. Considering their frequency of dining in casual restaurants, the researcher was able to gather significant data that concerned their criteria for chair selection when dining in restaurants. Meanwhile, through photo documentation, observation guide, and focus group discussion, the dining chairs were also assessed through personal experiences of the respondents on distinct chairs of related types of restaurants. Most of the respondents perception of comfort was based on major factors such as the aesthetics of the chair suggesting a greater guest comfort, its psychological impact to the diners, and the physical satisfaction of customers when dining in restaurants. Furthermore, the completeness of the chair components and its inclusivity to all types of users were also significant factors affecting their chair selection. With these considerations affecting comfortability of people, the researcher recommended that furniture designers of commercially used seating furniture should consider all possible conditions of the people by making the users feel more independent and reduce their stress or difficulties in times that they are not in their finest state, when designing chairs that will be used by various types of users.